Efficient Organic Light Emitting Diodes Using Solution-Processed Alkali Metal Carbonate Doped ZnO as Electron Injection Layer - Chen, Guo; Liu, Feiyang; Ling, Zhitian; Zhang, Pengpeng; Wei, Bin; Zhu, Wenqing (Frontiers in Chemistry, 2019)
In this study, we demonstrate a highly efficient inverted organic light-emitting diodes (IOLEDs) using solution-processed alkali metal carbonate doped ZnO as an electron injection layer (EIL) and tris-(8-hydroxyquinoline) aluminum (Alq3) as an emitter layer. In order to enhance the electron injection efficiency of the IOLEDs, the ZnO EIL layers were modified by doping various alkali metal carbonate materials including Li2CO3, Na2CO3, K2CO3 and Cs2CO3 by using low-temperature wet-chemical method. Compared to the control neat ZnO EIL-based IOLEDs, the alkali metal carbonate doped ZnO EIL-based IOLEDs possess obviously improved device performance. An optimal current efficiency of 6.04 cd A−1 were realized from the K2CO3 doped ZnO EIL based IOLED, which is 54% improved than that of the neat ZnO EIL based device. The enhancement is ascribed to the increased electron mobility and reduced barrier height for more efficient electron injection. Our results indicate that alkali metal carbonate doped ZnO has promising potential for application in highly efficient solution-processed OLEDs.